Tempo e teatralità nei film a soggetto teatrale - Pietrini, Sandra (Mimesis Journal, 2012)
The article explores the interaction between theater and cinema in films about theater, more specifically in relationship to the concept of time, in two different meanings: as a subject hinting to the passing of generations on the one hand and as a manipulation of a story on the other. As I will try to show, these very different perspectives can intersect and superpose, giving birth to negative or positive visions of the stage and theatricality. Theatricality can be a great resource (as in To Be or Not To Be by Lubitsch and Le carrosse d’or by Renoir) as well as a path of tragic circularity (as in O’ thiasos by Anghelopoulos or in films showing an artist’s decline, like Mankiewicz’s All About Eve). The films on theatre show an extreme variety of attitudes towards the stage, confirming the importance of this original and primitive model in the re-elaboration of time and space made possible by the new art of cinema.